Dual-Tracer Positron-Emission Tomography for Identification of Culprit Carotid Plaques and Pathophysiology In Vivo. (March 2020) - Evans, Nicholas R.; Tarkin, Jason M.; Chowdhury, Mohammed M.; Le, Elizabeth P.V.; Coughlin, Patrick A.; Rudd, James H.F.; Warburton, Elizabeth A.
Abstract : Background: Inflammation and microcalcification are interrelated processes contributing to atherosclerotic plaque vulnerability. Positron-emission tomography can quantify these processes in vivo. This study investigates (1) 18 F-fluorodeoxyglucose (FDG) and 18 F-sodium fluoride (NaF) uptake in culprit versus nonculprit carotid atheroma, (2) spatial distributions of uptake, and (3) how macrocalcification affects this relationship. Methods: Individuals with acute ischemic stroke with ipsilateral carotid stenosis of ≥50% underwent FDG-positron-emission tomography and NaF-positron-emission tomography. Tracer uptake was quantified using maximum tissue-to-background ratios (TBRmax ) and macrocalcification quantified using Agatston scoring. Results: In 26 individuals, median most diseased segment TBRmax (interquartile range) was higher in culprit than in nonculprit atheroma for both FDG (2.08 [0.52] versus 1.89 [0.40]; P <0.001) and NaF (2.68 [0.63] versus 2.39 [1.02]; P <0.001). However, whole vessel TBRmax was higher in culprit arteries for FDG (1.92 [0.41] versus 1.71 [0.31]; P <0.001) but not NaF (1.85 [0.28] versus 1.79 [0.60]; P =0.10). NaF uptake was concentrated at carotid bifurcations, while FDG was distributed evenly throughout arteries. Correlations between FDG and NaF TBRmax differed between bifurcations with low macrocalcification ( r s =0.38; P <0.001) versus high macrocalcification ( r s =0.59; P <0.001). Conclusions: This is the first study to demonstrate increased uptake of both FDG and NaF in culprit carotid plaques, with discrete distributions of pathophysiology influencing vulnerability in vivo. These findings have implications for our understanding of the natural history of the disease and for the clinical assessment and management of carotid atherosclerosis.